STRATEGI BISNIS OLEH-OLEH KHAS KENDARI DALAM MENINGKATKAN DAYA SAING DI KOTA KENDARI - Makmur Kambolong; Munawir Makmur; Candra Puspita Ningtyas; Luh Suwarningsih (Halu Oleo University, 2023)
In general, companies strive to meet consumer expectations, by building trust in a long-term relationship between the company and its customers. Looking at the current conditions, the increasing number of souvenir shops in the Kendari area could be a threat to the Kendari Souvenir Shop Typical Kendari Souvenirs and in the future, there will be shops that provide the same products and food as the Oleh Shop. -by Kendari Souvenirs Typical of Kendari. Therefore, the Kendari Typical Souvenir Shop, which is located right in a strategic area in the middle of Kendari City, must increase its competitiveness and implement or prepare a business strategy that is superior to its competitors and must be more careful in reading and anticipating market conditions and creating products that are superior to those of its competitors. quality. This research uses descriptive qualitative research methods. The research results show that the Kendari Souvenir Shop uses operational strategies to improve the management of goods, stock and product quality. Kendari Typical Souvenir Shop competes by emphasizing product excellence, satisfying customer service, and in-depth recognition of consumer tastes. They always provide innovation in products and services to maintain market position and increase consumer satisfaction.